Participation In Conducting The Visual Inspection Of Acetic Acid As An Early Detection Effort Towards The Servical Cancer Reviewed From Information Access and Knowledge - W. Winarni; Rina Sri Widayati; Sri Handayani (P3M Universitas 'Aisyiyah Surakarta, 2021)
Background : the problem of the reproduction health is appeared because of the lack knowledge for women about reproduction health such as hygiene problem which can lead to various diseases of reproductive organs, one of those is cervical cancer. This cancer places at the second rank after breast cancer as the most common cancer suffered by Indonesian women. It is noted that there are more than 270.000 women died because of the servical cancer and it is estimated about 40.000 new cases of its cancer in each year. Aim: this study is aimed to analyze the knowledge and information access with mothers’ participation in conducting the visual inspection of acetic acid. Method: the type of this study is an analytic observational research. The population is the couple of mothers in childbearing age of a study and communication forum for moeslem women in Pucangan. The sampling technique applies the saturated sample that fulfilling the inclusion criteria, totally 76 respondents. Data Analysis uses X2 for bivariate and logistics regression for multivariate. Result: there is a correlation of information access with the mothers’ participation in conducting visual inspection of acetic acid and there is a correlation of knowledge with the mothers’ participation in conducting visual inspection of acetic acid. Conclusion: knowledge and information access are including variables that can influence participation in the IVA test checkup are about 65.5% and the remaining are about 31.5% influenced by other factors outside the research model.